Managing the regressed left ventricle in late presenting TGA - Malankar, Dhananjay Prakash; Sharma, Rajesh (Indian journal of thoracic and cardiovascular surgery, 2025)
Introduction The arterial switch operation (ASO) remains the gold standard of care for neonates with transposition of great arteries (TGA). However, the timing and the choice of surgical procedure in children presenting late with transposition of great arteries with intact ventricular septum (TGA/IVS) and regressed left ventricle (rLV) is still a matter of debate. Evolution of the concept of left ventricular re-training with different techniques has led to a paradigm shift in the management of this subset of late presenting ‘simple’ transposition. Materials and methods Literature review was done in Pubmed and Scopus to identify relevant articles pertaining to the pathophysiology and different treatment options for late presenting TGA with intact ventricular septum with an aim of writing a review on the subject. Results Multiple treatment options have been reported in the literature varying from a single-stage operation to multi-stage procedure to achieve good long-term result. Majority are isolated case reports or case series with small number of children and only few studies have mid-term and long-term outcomes. Conclusions In children presenting late with TGA and rLV, left ventricular re-training seems the most feasible and effective method. In hospital setups with cost constraints, other low-risk techniques can be attempted but corrective surgery will be needed in the future, thus making these procedures cost-shifting strategies rather than cost-saving procedures.